THE INFLUENCE OF GREEN ACCOUNTING AND CORPORATE SOCIAL RESPONSIBILITY TOWARD PROFITABILITY - Maghfiroh, Faridatun; Sultoni, Mohammad Hamim; Abidin, Zainal (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research aims to analyze the influence of green accounting and corporate social responsibility (CSR) on company profitability partially and test and analyze the influence of green accounting and corporate social responsibility (CSR) on company profitability simultaneously. The population used in this research is 27 mining sector companies listed on the Indonesian Sharia Stock Index. The sampling technique in this research is purposive sampling, and there are 12 companies that meet the criteria as samples and there are 36 financial reports. The data analysis used is descriptive analysis, classical assumption testing, multiple regression analysis testing and hypothesis testing with the help of the SPSS 24 program.   The results of this research show that; First, variables green accounting The significance value obtained is 0.735 > 0.05 and the t value is 0.341 < 2.039 t table, so green accounting does not have a significant effect on profitability in mining sector companies for the 2020-2022 period. Second, the variable corporate social responsibility (CSR) obtained a significance value of 0.476 > 0.05 and a t value of 0.722 < 2.039 ttable, so corporate social responsibility (CSR) does not have a significant effect on profitability in mining sector companies for the 2020-2022 period. In the simultaneous test, the significance value is 0.738, which means the significance value is 0.738 > 0.05 and the f value is 0.307 < 3.30 ft, which means that green accounting and corporate social responsibility (CSR) simultaneously have no effect on profitability in mining sector companies for the 2020-2022 period